80.3k views
2 votes
If y = 2x and 3x - 3y = 2, then x =

User Exploring
by
5.3k points

1 Answer

2 votes

Answer:

The value of x is equal to -2/3.

Explanation:

In the problem it says that y equals 2x, and that 3x - 3y = 2.

The first step is to substitute 2x into y.

3x - 3(2x) = 2.

The next step is to use distributive property.

-3(2x) = -6x.

Now we need to add like terms.

3x - 6x = -3x.

Which gives us the equation -3x = 2.

The final step is to divide on both sides to get the value of x.

-3x/-3 = 2/-3.

x = -2/3.

So as you can see, x is equal to -2/3.

We can also check to make sure by redoing the problem, but substituting the value of x.

3(-2/3) - 3(2 * -2/3) = 2.

-2 - 3 * -4/3 = 2.

-2 + 4 = 2.

2 = 2.

The value of x is indeed -2/3.

User Lao Tzu
by
5.6k points